2021
DOI: 10.3390/foods10050961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl Replacement by other Salts on the Quality of Bísaro Pork Sausages (PGI Chouriça de Vinhais)

Abstract: Concerned about the trend to reduce salt consumption, the meat industry has been increasing the strategies to produce and commercialize products where the reduction or even the replacement of NaCl is an important goal. The aim of this study was to test the effect of partial NaCl replacement by KCl and Sub4Salt® on the quality of pork sausages. Three different formulations (NaCl + KCl, NaCl + Sub4Salt®, and KCl + Sub4Salt®) were considered and compared to the control (2% NaCl). Physicochemical properties, chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
3
10
1
1
Order By: Relevance
“…The total amount of TFA in meat ranging from 2-5% of the total fatty acid content [48] and the highest content was verified in GPF burgers (3.6%) below the cited range, since no other trans fatty acids were recorded. The content of elaidic acid in goat burgers was relatively higher than in other meat products with fat replacement by different oil emulsions [10,19,38,39,48]. However, in the present study, no other trans fatty acids were found.…”
Section: Physicochemical Properties and Chemical Compositioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The total amount of TFA in meat ranging from 2-5% of the total fatty acid content [48] and the highest content was verified in GPF burgers (3.6%) below the cited range, since no other trans fatty acids were recorded. The content of elaidic acid in goat burgers was relatively higher than in other meat products with fat replacement by different oil emulsions [10,19,38,39,48]. However, in the present study, no other trans fatty acids were found.…”
Section: Physicochemical Properties and Chemical Compositioncontrasting
confidence: 82%
“…The burgers with pork fat (GPF) have significantly lower water activity (a w ) than the burgers with olive oil (GOO), and the commercial burgers (CH) show an a w between the goat meat burgers. In any case, all burgers showed the characteristics of a perishable product with a shelf life between 24 and 48 h and with a w higher than 0.9 [4,6,38]. Significant differences were found for the color parameters between the goat burgers (GOO and GPF) and the CH burgers.…”
Section: Physicochemical Properties and Chemical Compositionmentioning
confidence: 82%
See 1 more Smart Citation
“…The combination of 5% yeast extract, 70% NaCl, and 30% KCl produced a reduced‐NaCl salmon which was sensorially accepted by consumers. The reduction of NaCl with a mixture of KCl + sub4Salt ® and NaCl + KCl did not impose a significant impact on the physicochemical properties, chemical composition, and sensory characteristics of pork sausages but achieved a significant decrement in NaCl by 22.7% and 16%, respectively (Teixeira et al ., 2021).…”
Section: Salt Substitutesmentioning
confidence: 99%
“…An important point about the addition of non-meat ingredients to replace or reduce fat, salt (NaCl), and/or nitrites in meat products is microbiological safety. The addition of vegetable oils in emulsions leads to the incorporation of water content in meat products, increasing the risk of microbial contamination [ 38 ]; the enzymatic and microbial inhibition of sodium chloride salt replacers could vary according to the replacer and the microorganism [ 39 , 40 ]; the diminution of nitrite, as a vital preservative in the meat industry, should also be compensated to limit the growth of pathogenic microbial, such Clostridium. Therefore, significant changes in microbiological populations of meat products because of reformulation are expected.…”
Section: Introductionmentioning
confidence: 99%